PENGARUH SISTEM PENGENDALIAN INTERNAL DAN AUDIT INTERNAL TERHADAP PELAKSANAAN GOOD CORPORATE GOVERNANCE - arifudin, opan; Juhadi, Juhadi; Sofyan, Yayan (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2020)
This research is conducted based on the recently viral phenomenon of the Good Corporate Governance issue, yet in reality there is also absence in full realization by state-owned institutions to implement it as the necessity and as its obligation in community service. This proves in several corruption cases which are revealed both in State-Owned Enterprise (BUMN) and Region-Owned Enterprise, especially in Bandung. The aim of this research is to identify the influence of internal control and internal audit to the implementation of Good Corporate Governance both directly and indirectly in BUMN and BUMD in particular in Bandung. This research uses the population of BUMN and BUMD in Bandung as many as 18 enterprises which consists of 14 BUMNs and 4 BUMDs. The method used for this research is analytical description with path analysis system. The results of this research show that the implementation of internal control and internal audit systems in BUMNs are significantly better than in BUMDs. This condition is caused by the rule of Good Corporate Governance binding the BUMNs to apply its organizational management better than in BUMDs. It also proves in statistical result that shows that internal control and internal audit systems have positive effects on the implementation of Good Corporate Governance. Directly, internal control system affects positively for 61.4%, while internal audit system does for 19.2%. Indirectly, both internal control and internal audit systems affect 80.6%. From this results showed, it can be concluded that internal control system in an organization supported by the efficiency of internal audit function will result in the satisfactory implementation of the Good Corporate Governance in the organization.